P117: Procedural skills training in emergency medicine physicians within the Edmonton zone: a needs assessment. (May 2019) - Schonnop, R.; Stauffer, B.; Gauri, A.; Ha, D.
Abstract : Introduction : Procedural skills are a key component of an emergency physician's practice. The Edmonton Zone is a health region that comprises eleven tertiary, urban community and rural community emergency departments (EDs) that represents over three hundred emergency physicians. We report the initial stakeholder and site leadership needs assessment used to inform the development of a comprehensive continuing professional development (CPD) procedural skills curriculum for the Edmonton Zone.Methods : A list of procedural skills was distributed to the two Edmonton Zone Clinical Department Heads of Emergency Medicine (EM). This list was based on a previous Canadian study that utilized procedures from the Objectives of Training in EM. Based on perceived needs, twenty-five procedures were chosen by consensus from zone leadership and study authors as the initial focus for a skills curriculum. This list was sent via survey to the physician site leads of all EDs in the zone. Each site lead was asked to indicate the fifteen procedure curriculum they felt would most benefit their respective physician groups. Responses were collated to look at all departments as a group and stratified by the type of ED (tertiary, urban and rural community).Results : Every site chief of Edmonton Zone EDs completed the survey (100% response rate). Cricothyrotomy and pediatric intubation were the two procedures prioritized by every site. One procedure (ultrasound guided central lines) was prioritized by 10/11 sites while three procedures (ultrasound guided central lines, adult intubation and chest tube insertion) were specified by 9/11 sites as needs. Two procedures (pericardiocentesis and thoracotomy) were named as priorities only by tertiary centers. Conversely, three procedures (extensor tendon repair, anterior and posterior nasal packing) were highlighted by all rural sites, but not consistently by any urban sites.Conclusion : Over the next few years, competency-based CPD will emerge for physicians in practice. Our preliminary needs assessment showed that while a common zone-wide curriculum will be possible, targeted curricula tailored to the unique needs of the various types of EDs will also be necessary. This has implications for the resources and teaching requirements needed to deliver effective and recurring CPD courses to an entire health region. A targeted needs assessment to all Edmonton Zone physicians will be the next step to verify and further elaborate on these preliminary results.